Relationship between ABCB1 polymorphisms and serum methadone concentration in patients undergoing methadone maintenance therapy (MMT) - Nasir, Mohamad; Zalina, Zahari; Lee, Chee Siong (Taylor and Francis Ltd, 2016)
Background: Methadone is a substrate of the permeability glycoprotein (P-gp) efflux transporter, which is encoded by the ABCB1 (MDR1) gene. Large interindividual variability in serum methadone levels for therapeutic response has been reported. Genetic variations in ABCB1 gene may be responsible for the variability in observed methadone concentrations.